2013
DOI: 10.1021/nn402563f
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Drugs of Abuse in Saliva Using Surface Enhanced Raman Spectroscopy and Microfluidics

Abstract: We present a microfluidic device that detects trace concentrations of drugs of abuse in saliva within minutes using surface-enhanced Raman spectroscopy (SERS). Its operation is demonstrated using methamphetamine. The detection scheme exploits concentration gradients of chemicals, fostered by the laminar flow in the device, to control the interactions between the analyte, silver nanoparticles (Ag-NPs), and a salt. Also, since all species interact while advecting downstream, the relevant reaction coordinates occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
166
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(169 citation statements)
references
References 35 publications
1
166
0
2
Order By: Relevance
“…28 Andreou et al also reported the detection of methamphet-amine in saliva samples using a microfluidic device which controlled the interaction between the drug, Ag nanoparticles, and the aggregation agent. 29 Finally, in a more recent study, we have also demonstrated SERS as a powerful technique for the quantitative detection of the beta-blocker propranolol in human biofluids (serum, plasma, urine) when combined with chemometric approaches. 30 However, the application of SERS for the detection and quantification of drugs in complex biological media can face several challenges, most notably the reproducibility, accuracy and repeatability of the SERS signal which could be due to ran-domly distributed hot spots which occur during sample ana-lysis.…”
Section: Introductionmentioning
confidence: 88%
“…28 Andreou et al also reported the detection of methamphet-amine in saliva samples using a microfluidic device which controlled the interaction between the drug, Ag nanoparticles, and the aggregation agent. 29 Finally, in a more recent study, we have also demonstrated SERS as a powerful technique for the quantitative detection of the beta-blocker propranolol in human biofluids (serum, plasma, urine) when combined with chemometric approaches. 30 However, the application of SERS for the detection and quantification of drugs in complex biological media can face several challenges, most notably the reproducibility, accuracy and repeatability of the SERS signal which could be due to ran-domly distributed hot spots which occur during sample ana-lysis.…”
Section: Introductionmentioning
confidence: 88%
“…As the number of analytes increases, it is appropriate to introduce selectivity in the SERS methodology, which commonly is supported by powerful algorithms and chemometric based analyses. A remaining challenge is to introduce sufficient selectivity to resolve signals from an interfering matrix, as for example for drugs in saliva [16][17][18] or antibiotic substances [19] and nicotine [20] in urine. The first step towards this goal is to obtain SERS substrates that are giving rise to reliable, reproducible and satisfying detection limits in the analytical set-up.…”
Section: Introductionmentioning
confidence: 99%
“…For testing narcotics at home, commercial drug-screening products are available using the Marquis reagent and a similar colorimetric reaction. However, this method requires specialized reactants, large sample volumes and is open to misinterpretation due to subjective color perception (Andreou et al, 2013). These disadvantages prompt the investigation of rapid and on-site assays for monitoring trace level drugs in biological fluids.…”
Section: Introductionmentioning
confidence: 99%